1998
DOI: 10.1681/asn.v94614
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-1 in renal ischemic reperfusion injury.

Abstract: Interleukin-1 (IL-1) is a central component of many acute inflammatory processes. Blocking IL-1 receptor (IL-1R) with IL-1R antagonist (IL-1Ra) has attenuated ischemic reperfusion injury in brain, heart, and liver models. However, the role of IL-1 in renal ischemic reperfusion injury (IRI) is not known. Therefore, the role of IL-1 in renal IRI was evaluated using the complementary approaches of IL-1R blockade in wild-type mice in addition to the study of renal IRI in IL-1R knockout (KO) mice. Ischemia was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Among these, PARP1 appeared to have protective renal effects in knock-out mouse models of ischemic injury [25]. In contrast to PPAR1, IL1R1 (interleukin receptor 1) resulted in lower creatinine blood concentrations in models of ischemic injury [26].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, PARP1 appeared to have protective renal effects in knock-out mouse models of ischemic injury [25]. In contrast to PPAR1, IL1R1 (interleukin receptor 1) resulted in lower creatinine blood concentrations in models of ischemic injury [26].…”
Section: Discussionmentioning
confidence: 99%
“…For example, IL-1R1 blockade failed to attenuate murine ischemic AKI but mitigated renal tubular damage and apoptosis in a rat model of renal IRI. 6,61 While the reasons for some discrepant effects of IL-1R1 receptor antagonism versus deficiency are unclear, our findings in this study offer one explanation that IL-1 signaling may exert cell lineage–specific opposing roles in acute renal damage.…”
Section: Discussionmentioning
confidence: 71%
“…Kelly et al reported that the gene-deficient adhesion molecule ICAM-1 could protect against renal injury in an animal model of renal ischemia ( Kelly et al, 1996 ). In addition, renal tubular epithelial cells can also contribute to the inflammatory response to renal IR injury by producing various pro-inflammatory cytokines (e.g., TNF-α, IL-1β) and chemokines (e.g., MCP-1) ( Haq et al, 1998 ; Sung et al, 2002 ; Spurgeon et al, 2005 ). In the present study, pro-inflammatory cytokines and cell adhesion molecules were decreased in vitro and in vivo following MA administration, indicating that MA may ameliorate IRI by inhibiting the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%